Corporate Governance Factors Drive Firms’ Earning Per Share: Evidence from Pakistan Stock Exchange Listed Companies - YASIR KHAN; MUHAMMAD AMJAD; DR.SAIMA BATOOL; OBAID ULLAH BASHIR (Journal of Business & Tourism, 2021)
The aim of this study is to examine the corporate governance factors that drive the firms’ earning per share (EPS) sample of firms listed on Pakistan Stock Exchange (PSX) over the period of 2011 to 2016. This paper analyzed the impact and relationship of dependent variable (Earning per Share) and independent variables (Board Independence, Ownership concentration, CEO duality and Board diversity). The panel data collected from the sample of top 20 companies (market capitalizations) listed in Pakistan stock exchange. To investigate the relationship between variables the Pearson correlation and regression applied and to identify the impact of independent variables (board independence, ownership concentration, CEO duality and Board diversity) on dependent variable (earning per share) used regression tool. The study result of correlations and regression result revealed that board independence, ownership concentration and Board diversity have significant impact on performance while CEO Duality has negative impact on Firm financial performance.